Kaarl–ka–Nyininge, A Place to be: We’re sitting here around the fire. A Creative Anthology of Nyoongar Women’s Oral Histories of Brookton - Hayden, Elizabeth (Curtin University, 2024)
This thesis describes a Nyoongar cultural framework of ‘belonging’. It is written using a Storyteller’s voice. The characters in these stories share their voices– my Elders and ancestors: my sister Janet, my mother Martha, my grandfather, and me. Together, our voices call back the history of Brookton, a Nyoongar telling of the place I call home, Kaarl-ka-nyininge. A once silenced history, now told for others so they may bear witness in their journey to reconciliation.